Hyperbaric oxygen therapy and the critically ill patient - Santos, Daniel José; Araújo, Rita; Araújo, Ana Carolina (Journal of the Portuguese Society of Anesthesiology, 2024)
Introduction Many of the accepted indications for treatment with hyperbaric oxygen therapy may occur in the critically ill patient. Given its increasing use, it is urgent to review the current literature and adapt the international guidelines to the portuguese reality. Material and Methods A non-systematic literature review completed in May 2023 is presented. The PubMed database was used with the following MeSH search terms: hyperbaric oxygen therapy, hyperbaric oxygenation, critically ill, intensive care, critical care. We reviewed all articles that cited the most recent recommendations for the approach of the critically ill patients in hyperbaric environment of the European Committee for Hyperbaric Medicine of 2017. Results After the initial search, 51 publications were obtained. After reading the titles of the articles, 29 articles were selected. Subsequently, 9 articles were excluded: 5 due to unavailable abstract, 3 due to the scope of the article not related to the theme and 1 for being a publication of the study protocol. The selection was made based on the relevance of the topic and the methodology used. Discussion The treatment of critically ill patient with hyperbaric oxygen therapy requires specialized equipment and personnel with competence in intensive care and hyperbaric medicine, with knowledge of the physiology and risks of hyperbaric oxygen therapy. Hyperbaric medicine centers have specific and different characteristics in terms of location, type of chambers, environment and safety. On the other hand, the critically ill patient also requires specific monitoring and treatment conditions. Hyperbaric oxygen therapy should never delay or stop the overall approach to the critically ill patient. Patient monitoring or ongoing treatments should not be altered or interrupted. Any effect of this therapy should be strictly evaluated and appropriately mitigated. Hyperbaric treatments can be safely administered to the critically ill patient. Conclusion It is estimated that an increasing number of critically ill patients may be referred and benefit from hyperbaric treatments. Hyperbaric oxygen therapy should be included in the management of patients in the Intensive Care Unit whenever the benefits generated outweigh the potential risks, not delaying or interrupting concomitant treatments.